The OPERAS-PL development strategy for local open scholarly communication - Wnuk, Magdalena; Świetlik, Marta (Septentrio Conference Series, 2022)
OPERAS is a European consortium-based research infrastructure for the social sciences and humanities (SSH). It has been established as an non-commercial initiative aimed at transforming the European research area of scholarly communication and therefore it is targeted at researchers, librarians, publishers and infrastructure providers in over a dozen of European countries. This rich and diverse group of stakeholders is the key to OPERAS’s success. The proposed poster will discuss this leading idea on the example of the OPERAS-PL – the Polish national node of the infrastructure. Maintenance of infrastructures, or simply speaking: digital tools and services facilitating scholarly communication, is certainly one of the biggest challenges from the economic point of view (Edmond, 2020). However, the other challenging aspect is actually making truly useful, used and vivid tools, adjusting to stakeholders’ needs and fulfilling them (Anderson, 2013; van Zundert, 2012). One of OPERAS’s strategic plans for this to happen is the network of national nodes established in each of the partner countries (Consortium OPERAS, 2022). The nodes’ primary goal is to disseminate OPERAS services, attract users and involve new partners. However, their mission should be perceived wider. As national points of contact they actually may become the levers of the whole infrastructure’s development and perseverance – similarly to DARIAH-EU (the Digital Research Infrastructure for the Arts and Humanities) whose sustainability relies precisely on its scattered and bottom-up structure (Edmond, 2020). Our poster presents the development strategy for the Polish National Node OPERAS-PL, along with its mission, primary goals and milestones, targeted audiences, funding scheme, management methods and tools and risk mitigation. The strategy is analysed as a scalable model for similar initiatives which strive to enhance open scholarly practices in their respective communities. The poster builds on the recently launched project funded by the Polish Ministry of Education and Science and introduces two pilot research pursuits aiming at recognising the needs of the Polish SSH communities. The first pilot will study academic publishers’ needs in the field of open access. Through a design thinking technique we will recognise their needs and create a sustainability model for open access book publishing that will accomodate the specificity of Polish stakeholders. The second one will examine the potential of digital monographs as equivalent to traditional monographs in the Polish academic evaluation system. We will use our infrastructure for digital editions and adapt it to address the needs of book authors and publishers. The results of the pilots will be disseminated in the coming years at the Munin Conference on Scholarly Publishing and other events.